Feasibility study of monopile-friction wheel-bucket hybrid foundation for offshore wind turbine. (15th May 2020) - Li, Xinyao; Zeng, Xiangwu; Wang, Xuefei
Abstract: In this study, a hybrid monopile-friction wheel-bucket (MFB) foundation for offshore wind turbines is proposed. A bucket and a friction wheel are integrated with a monopile. The friction wheel is filled with scattered material to provide distributed surcharge loads to the subsoil. A series of geotechnical centrifuge tests was performed under monotonic load and cyclic load to investigate the bearing capacity of the MFB foundation. Five hybrid foundations with variable dimensions were tested in four types of sandy soil conditions. The centrifuge test results show that the ultimate bearing capacity of the hybrid MFB foundation could be 4 times of the monopile foundation. Under cyclic load, the final displacement of MFB foundation is significantly smaller than that of the monopile foundation. The MFB foundation is stiffer in the reloading process but shows slightly more plastic characteristic in the unloading process. The size of the add-on friction wheel-bucket structure is positively related to the performance of the MFB foundation. The bucket height tends to be a more effective factor. It is illustrated that the MFB foundation tends to demonstrates more improvements in the saturated loose sand. A simplified method is proposed to predict the bearing capacity of the hybrid MFB foundation. Highlights: An innovative monopile-friction wheel-bucket hybrid foundation is proposed. Bearing behavior of offshore wind turbine with the innovative hybrid foundation is investigated. Centrifuge tests are performed under ultimate and service conditions. An analytical method is put forward to predict bearing capacity.